2022
DOI: 10.1038/s41598-022-20915-z
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial infiltration and detorque at the implant abutment morse taper interface after masticatory simulation

Abstract: This study evaluated the bacterial infiltration and the detorque of indexed and non-indexed abutments of Morse taper implants (MTI) after mechanical cycling (MC). 40 MTI were distributed into four groups: IIA (indexed implant abutments); NIIA (non-indexed implant abutments); IIAMC (indexed implant abutments submitted to MC); NIIAMC (non-indexed implant abutments submitted to MC), which were carried out under one million 5 Hz frequency and 3 Bar pressure. After mechanical cycling, all groups were immersed in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
(40 reference statements)
0
0
0
Order By: Relevance
“…After the preload during the installation of the abutments, which is done by applying a torque determined by the manufacturer, these sets should remain stable during the application of masticatory loads. However, as described in previous studies [8], in most systems (IA sets) there is accommodation of the parts during the application of loads that can change the initial torque applied and, consequently, change the stability of the sets. In addition, non-tapered IA sets (external and internal hexagon connections) may exhibit micromovements during the application of forces [9].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…After the preload during the installation of the abutments, which is done by applying a torque determined by the manufacturer, these sets should remain stable during the application of masticatory loads. However, as described in previous studies [8], in most systems (IA sets) there is accommodation of the parts during the application of loads that can change the initial torque applied and, consequently, change the stability of the sets. In addition, non-tapered IA sets (external and internal hexagon connections) may exhibit micromovements during the application of forces [9].…”
Section: Introductionmentioning
confidence: 90%
“…On the other hand, other studies evaluated whether the inclusion of the index could affect bacterial sealing and the resistance of the IA sets, since it results in a decrease in the contact area in the conical portion of the implant/abutment. Based on methodologies for evaluating bacterial microleakage and resistance to fracture, the authors observed that the presence of the index did not compromise the performance of MT implants [8,9,11].…”
Section: Introductionmentioning
confidence: 99%